Neoliberalism's true heirs: What late-apartheid South Africa can teach us about the contemporary far right - Elizabeth Freda Soer (Max Planck Institute for the Study of Societies, 2025)
How can we make sense of the resurgence of the far right across the world? From the re-election of Donald Trump to the flourishing of Hindu nationalism under Narendra Modi, right-wing politicians have undoubtedly grown in prominence over the last decade. There is a burgeoning literature on this topic as scholars attempt to understand whether it is a backlash against neoliberalism, a reactionary form of neoliberalism, or simply a cultural phenomenon produced by increased global connectivity. This paper contributes to the vibrant discussion by examining an ideal yet overlooked case of ethno-nationalist neoliberalism - apartheid South Africa in the 1980s. This case reveals neoliberalism's relationship to colonialism and its contribution to the perpetuation of white rule. South Africa has served as a test case for neoliberal ideas about race and economics and can thus contribute broader insights on the topic. The paper argues that the contemporary far right is not a backlash against neoliberalism, but a robust continuation of it. It draws on a vast range of archival sources from the late-apartheid period as well as the writings of prominent neoliberal thinkers to support this argument. – – Wie ist das Wiedererstarken der extremen Rechten auf der ganzen Welt zu verstehen? Von der Wiederwahl Donald Trumps bis zum Aufblühen des Hindu-Nationalismus unter Narendra Modi: Rechte Politik hat im Laufe der letzten zehn Jahre zweifellos an Einfluss gewonnen. Entsprechend wächst die Anzahl der wissenschaftlichen Veröffentlichungen, die sich mit der Frage beschäftigen, ob es sich um eine Gegenreaktion auf den Neoliberalismus, eine reaktionäre Form des Neoliberalismus oder um ein aus zunehmender globaler Vernetzung resultierendes kulturelles Phänomen handelt. Dieser Aufsatz behandelt die Apartheid in Südafrika in den 1980er-Jahren und leistet damit einen Beitrag zur aktuellen Debatte. Südafrika ist ein oft übersehenes, aber ideales Beispiel für ethnonationalistischen Neoliberalismus, weil es die Beziehung des Neoliberalismus zum Kolonialismus und seinen Einfluss auf die Aufrechterhaltung der weißen Herrschaft offenbart. Es kann wegen seiner neoliberalen Vorstellungen von Rasse und Wirtschaft zu umfassenderen Erkenntnissen in diesem Zusammenhang beitragen. Der Aufsatz argumentiert, dass die heutige extreme Rechte keine Gegenreaktion auf den Neoliberalismus darstellt, sondern eine robuste Fortsetzung davon ist. Eine Vielzahl von Archivquellen aus der Zeit der späten Apartheid sowie Schriften prominenter neoliberaler Theoretiker untermauern dieses Argument.
hdl:21.11116/0000-0010-FD2B-2
Keywords: 300; ethno-nationalism; far right; neoliberalism; South Africa; Ethnonationalismus; Neoliberalismus; Rechtsextremismus; Südafrika